(untitled) (Philological Studies, 2020)
The paper starts by tracing the shifts in the status of Anđelko Krstić in the framework of Serbian and Macedonian literature. We interpret the possibility of Krstić being unconditionally accepted as an author with more than one homeland as a non-ideological principle of literary history that could be involved in a de- traumatization of the past and the creation of a conflict-free future. The similarities in the depiction of migrant workers in the novels Trajan by Anđelko Krstić and Infidelity by Dejan Trajkoski are marginal when compared to the involvement of contemporary novelistic protagonists in the modernization processes which open the affected individuals to the experiences of the Other. However, we conclude with the observation that the discrete historical context of Infidelity reproduces memory narratives that perceive their subject solely as a victim of collective trauma in the past. Although Infidelity contains elements of an invigorating relativization of memory, it is influenced by dominant discourses that abandoned multi-perspectives of the Balkan past and the inclusion of the Other. Such multifaceted perspectives which include the Other represent a prerequisite for a conflict-free future of the Balkan peoples and cultures.